The control agenda : a history of the Strategic Arms Limitation Talks - Ambrose, Matthew J. (Cornell University Press, 2018)
The Control Agenda is a sweeping account of the history of the Strategic Arms Limitation Talks (SALT), their rise in the Nixon and Ford administrations, their downfall under President Carter, and their powerful legacies in the Reagan years and ...